Active balancing system in battery management system for Lithium-ion battery - Ness, Stephanie; Boujoudar, Younes; Aljarbouh, Ayman; Elyssaoui, Lahcen; Azeroual, Mohamed; Zahra Bassine, Fatima; Rele, Mayur (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The existing battery management systems perform many functions, such as simply monitoring the battery's voltage, current, and temperature for the most basic and compensating energy imbalances between battery cells for the most advanced systems. In this last example, the function balancing helps protect the battery from obtaining a better lifespan. However, these systems with such functions remain complex because they involve techniques specific to power electronics and energy conversion. The number of components, implementation complexity, and cost increased. The work presented in this paper fits directly into this context. The main objective is to provide a solution to the problem of battery management and careful pack cell balancing. The proposed system aims to balance the battery pack cells based on the intermediate state of charge by charging or discharging the imbalanced cell. The implementation of the proposed control strategy was for a battery pack composed of five cells under MATLAB/Simulink.